2002
DOI: 10.1007/s005340200020
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of common bile duct stones: transcystic approach and choledochotomy

Abstract: The purpose of this study was to review our experience with laparoscopic common bile duct (CBD) exploration by the transcystic approach and choledochotomy. We selected the transcystic approach for patients whose CBD stones were less than five in number and smaller than 9 mm in diameter, and whose CBD was less than 15 mm in diameter on cholangiograms. Among 217 patients with CBD stones treated laparoscopically, the transcystic approach was performed successfully in 91 of 104 patients in whom it was attempted (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 23 publications
3
88
2
1
Order By: Relevance
“…Indeed, these complications were observed in a case series of choledochotomy in 42% of patients [8][9][10]. In the present study no postoperative pancreatitis was observed, while bile leakage developed in one patient only.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Indeed, these complications were observed in a case series of choledochotomy in 42% of patients [8][9][10]. In the present study no postoperative pancreatitis was observed, while bile leakage developed in one patient only.…”
Section: Discussionsupporting
confidence: 54%
“…However, other series did not show such results [3,4]. The rate of residual stones after laparoscopic treatment ranges from 2.6% to 8% (mean 5%) and is equivalent to that of open surgery [3,7,8]. The transcystic approach, which is recently preferred in laparoscopic CBD exploration, is used in 26-93% (mean 71%) of cases, with a success rate ranging from 74% to 98% [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In these unclear situations both transcystic laparoscopic CBD exploration and sequential ERCP-ES are questionable as often related to dense biliary sludge associated with stenosis of the papilla in which ES is certainly the safest solution for the patient. The laparoscopic CBD exploration normally consists of major biliary surgery and needs higher laparoscopic skills and prolongs the duration of the entire operation also increasing the overall risk for the patient [18,19,27] . The mean prolongation of the time of RV is nor mally shor ter than those repor ted for totally laparoscopic CBD exploration [27,28] .…”
Section: Discussionmentioning
confidence: 99%
“…The laparoscopic CBD exploration normally consists of major biliary surgery and needs higher laparoscopic skills and prolongs the duration of the entire operation also increasing the overall risk for the patient [18,19,27] . The mean prolongation of the time of RV is nor mally shor ter than those repor ted for totally laparoscopic CBD exploration [27,28] . This difference becomes more evident for those patients with multiple large stones and sludge and problems at the papilla.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes are relatively similar to those observed in other studies. 5,6,8,10,13 According to the data from multivariate analysis, the serum BIL and the presence of MRFs were significantly associated with adverse outcomes. The presence of toxic substances, such as BIL and bile salts, impaired liver function, and altered nutritional status due to obstructive jaundice have been characterized as factors for the development of complications, including acute renal failure, cardiovascular depression, hemorrhage from vitamin K deficiency and septicaemia.…”
Section: Discussionmentioning
confidence: 99%